Pembuatan Motif Pada Kerudung Pasmina Dengan Teknik Ecoprint - Atina Khoiron Nisa; chairunisa Wiji Hidayati; Farida Ilmayanti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research explained about ecoprint exploration using young teak leaves on pashmina. The ecoprint technique is usually applied to natural fibrous materials, called cotton. The color results tend to be lighter and the leaf bone motifs are more visible, namely purple with the code #800080 and medium orchid with the code #ba55d3. The ecoprint coloring technique is done using the steam method and produces a beautiful and fashionable pashmina veil.